When art isn't real the world's most controversial objects under investigation - Shortland, Andrew; Degryse, Patrick ca. 20./21. Jh (Leuven University Press, 2022)
The art world is a multi-billion-dollar industry which captures world headlines on a regular basis, for both good and bad reasons. This book deals with one of the most-discussed areas of controversy: high-profile objects that have experts arguing about their veracity. Some may have been looted, others may be fakes, some may be heavily restored or misattributed. Often, in these cases, analytical science is called on to settle a dispute. The authors of this book have decades of experience in this field, working on a range of objects dating from prehistory to the twentieth century. They present seven of the most famous cases from the Getty Kouros to the Turin Shroud some of which are still contested, and examine how a few words from a connoisseur or scientist can make a virtually valueless object worth hundreds of millions. And vice versa
Keywords: Kunstmarkt; Fälschung; Antiquität; Expertise; Kunst; Forgery of antiquities; Art / Forgeries; Antiquities / Valuation; Antiquités / Faux; Art / Faux